Who, why, when and how do people use urban green spaces? A study of users from 18 parks in France. (13th November 2019) - Porcherie, M; Faure, E; le Gall, A Roué; Vaillant, Z; Thomas, M F; Rican, S; Héritage, Z; Bader, C; Simos, J; Cantorregi, N
Abstract: Introduction: Urban green spaces impact the individual and collective health of populations. At the city level, they act as regulators of environmental hazards and constitute collective protective factors. At the individual level, they constitute social spaces for encounters and rejuvenation. But, these functions depend on the use made of these green spaces which can be inequitable. This paper presents the results of the analysis of the use of green spaces in the 6 French cities selected in the WHO French Healthy City Network conducted as part of the GREENH-City research project. Methods: Based on park profiles, a qualitative survey was conducted among users of 3 different parks in each of the 6 selected cities with both observations and semi-directive interviews. Thematic analyzes were performed. Observed activities were classified into 8 groups (supervised educational, food, activities i.e. calm, commercial, artistic and cultural, physical non-sport, sports) and related to a specific use (professional/ personal, individual/ collective, authorized/ not and conflictual/ not). The uses described by the individuals interviewed were classified into 4 categories: attendance, utility, opinions and activities. Results: 186 observations and 591 recorded and unrecorded interviews with individuals or groups were conducted in the 18 parks. Overall, calm activities are dominant. However, activities and uses differ between cities and within the city depending on the nature of the parks (ancient, new..), their management, their location (more or less central, located in a deprived area or not) and people expectations. Conclusions: Park uses are only partially dependent on amenities within the park. The nature of the park itself, its geographical location and its landscape characteristics seem to be decisive for the uses observed. These data are essential to inform public decision-makers and guide the creation and development of green spaces in cities in a vision of social justice. Key messages: Urban green spaces can improve population health but their uses may be inequitable. Study of population use of urban green spaces may help to shape local policies towards more equity.